C Bank Chongqing Branch credit risk management research - Liu, Yue (2016)
For large financial institutions, credit risk has been the biggest problem of its development. At present, the credit risk management in the international large-scale financial institutions has formed a complete set of theoretical system and measurement model. Compared with them, there is still a big gap between China's and foreign financial institutions and commercial banks in this area. Therefore, the measurement and evaluation of the credit risk of China's commercial banks is a topic of concern and discussion in the academic and financial system. How to make more effective management of credit risk and constantly improve the efficiency of credit risk management of commercial banks is also one of popular topics of extensive research.